2021
DOI: 10.1002/smi.3108
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of resource recovery from physical and relaxation work break activities

Abstract: Actual resource replenishment, a defining part of the stress-recovery process, has hardly been studied. We address this gap in the literature within the context of work breaks to determine which resources are replenished relative to a pre-stressor baseline. Guided by conservation of resources theory and the effort-recovery model, we explored how two different break activities promoted recovery by looking at their effects on recovery experiences (relaxation, psychological detachment), psychological resources (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
(180 reference statements)
2
4
0
Order By: Relevance
“…In the path model, the total effect of relaxation breaks on energetic arousal was just not significant, there was only a significant bivariate correlation between relaxation breaks and energetic arousal. The finding that activity breaks outperformed relaxation breaks regarding the mood subdimension of energetical activation corresponds to the results from the experimental study by Hoover et al ( 2022 ), in which physical activity breaks were related to higher energy levels than relaxation breaks. Thus, physical activity may be particularly beneficial for replenishing energy resources.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the path model, the total effect of relaxation breaks on energetic arousal was just not significant, there was only a significant bivariate correlation between relaxation breaks and energetic arousal. The finding that activity breaks outperformed relaxation breaks regarding the mood subdimension of energetical activation corresponds to the results from the experimental study by Hoover et al ( 2022 ), in which physical activity breaks were related to higher energy levels than relaxation breaks. Thus, physical activity may be particularly beneficial for replenishing energy resources.…”
Section: Discussionsupporting
confidence: 87%
“…Cross-sectionally, light (e.g., stair climbing) and moderate (e.g., walking during lunch breaks) physical activities at work are associated with a lower need for recovery (Coffeng et al, 2015 ). Taking an experimental approach, Hoover et al ( 2022 ) recently showed that a physical activity break after induced resource depletion resulted in higher energy levels than relaxation breaks, while relaxation breaks resulted in higher detachment and relaxation than the physical activity break. Overall, energy levels after recovery break activities lasting 15 min returned to baseline, indicating the replenishment of lost resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… González-Hernández et al (2019) advocated that the development of psychological resources should be taken into account for teenagers’ perfect way of doing sports. Supporting this point, our study showed that increased engagement in physical activity could help one focus on the self, physically and psychologically, which enriched psychological resources like promoted perceived meaning ( Hooker and Masters, 2016 ) and self-efficacy ( Suorsa et al, 2016 ), and could also facilitate recovery from the depletion of psychological resources ( Hoover et al, 2021 ). In addition, our findings also approve the theoretical viewpoint that meaning and self-efficacy are two crucial psychological assets to deal with the stressful situation of the COVID-19 pandemic ( Cataldi et al, 2021 ; Talsma et al, 2021 ; Yu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 55%
“…However, individuals take action to compensate for this reduction, for instance, through recovery experiences (Sonnentag & Fritz, 2007; S. Zhang et al., 2022). An experimental study has shown that recovery experiences may increase psychological resources such as energy (Hoover et al., 2021). This compensation may be a protective factor against the adverse effects of resource reduction (Hao et al., 2022).…”
Section: Background and Hypothesesmentioning
confidence: 99%